Tratamiento de límite y borde del área de protección ecológica La Calzada, Saquisilí - Cajas Almache, Juan Carlos (2022)
The present investigation analyzes the social, territorial, and environmental transformation of the Saquisilí city, evidencing a vertiginous urban growth made up of informal settlements mainly on the periphery, on the boundary and border of the city, between the built and the natural, putting at risk ecological protection areas, particularly in the APE La Calzada. The research project delves into urban design, planning and territorial ordering, allowing territorial, productive development, and sustainable habitat to improve the quality of life of the population. The boundary and border study exposes the complexity in the treatment of informal settlements on the edge of the city, for which a methodology is developed that allows an answer to the social, territorial, and environmental transformations of the city. As a result of the research through urban reading, macro-scale achievements are obtained with a proposal for a master plan of the city called APE 2230 and a micro-scale achievement with a proposal for urban project strategies for the treatment of the boundary and border of the ecological protection area “La Calzada” called Sustainable Urban Border, planned to be developed over the course of 8 years corresponding to 2 administrative periods and focused on a sustainable urban territorial ordering, where the presence of 9 structuring projects or alternative scenarios is concluded